A Co‐catalyst‐Loaded Ta3N5 Photoanode with a High Solar Photocurrent for Water Splitting upon Facile Removal of the Surface Layer1. Issue 42 (14th August 2013) - Li, Mingxue; Luo, Wenjun; Cao, Dapeng; Zhao, Xin; Li, Zhaosheng; Yu, Tao; Zou, Zhigang
<x xml:space="preserve">Abstract</x> Surface exfoliation: A Ta3N5 photoanode prepared by a thermal oxidation and nitridation method shows a high solar photocurrent. This photocurrent is currently the highest achieved by a Ta3N5 photoanode. The photocurrent is obtained mainly because of facile thermal and mechanical exfoliation of the surface passivation layer of the Ta3N5 photoanode (see picture).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>